Effects of isopropanol ratio at different excess air ratios on combustion and emissions characteristics of an isopropanol/gasoline dual-fuel combined injection SI engine. (1st February 2023) - Li, Decheng; Yu, Xiumin; Guo, Zezhou; Zhang, Jufang; Wang, Tianqi; Li, Yanwei
Highlights: An injection mode of isopropanol direct injection plus gasoline port injection is proposed. Isopropanol can optimize combustion in the cylinder. Isopropanol can improve power performance and operation stability. Isopropanol can decrease unburned HC emissions, CO emissions and NOx emissions. Isopropanol hoists the ability of the engine operating under lean-burn conditions. Abstract: Energy crises and environmental issues require the development of green fuels for engines. Isopropanol is an excellent performance renewable alternative fuel for SI engines. It can be prepared by IBE fermentation. However, there have been few studies on the use of isopropanol/gasoline dual fuel in SI engines, especially based on the combined injection technology. For dual-fuel engines, the combined injection technology can further achieve clean combustion by flexibly controlling the fuel composition in the cylinder. Therefore, it is significant to combine the isopropanol/gasoline dual-fuel with the combined injection technology. The effects of the isopropanol ratio at different λ values on combustion and emissions characteristics of an isopropanol/gasoline dual-fuel combined injection SI engine were studied in this paper. The injection mode is isopropanol direct injection plus gasoline port injection. Six isopropanol ratios (0 %, 20 %, 40 %, 60 %, 80 %, 100 %) and five λ values (0.9, 1, 1.1, 1.2, 1.3) are set. The engine was tested at 1500 rpm with an intake pressure of 50 kPa. It is shown that isopropanol addition improves combustion, increases Pmax and maximum heat release rate, and shortens ignition delay period, rapid combustion period, and combustion duration. As the isopropanol ratio increases, the IMEP increases and the COVIMEP decreases. The improvements in combustion, IMEP and COVIMEP brought by the addition of isopropanol were more obvious under lean-burn conditions. Isopropanol addition effectively reduces unburned HC emissions, CO emissions, and NOx emissions. A higher isopropanol ratio in the mixture leads to better power and emissions performance. Isopropanol is a promising alternative fuel for engines, but its corrosive properties can damage the rubber parts of engines.